The Accused Poor - Headworth, Spencer (Social justice, 2017)
The article deals with the legal environments encountered by poor people in criminal adjudication and in welfare fraud proceedings in the U.S. Topics discussed include the absence of protections for criminal defendants in both criminal and administrative settings, the procedures involved in providing access to fair hearings, and the outcomes for the accused poor.